Solidifikasi Sludge Instalasi Pengolahan Air Limbah Industri Makanan Ringan - Prisca Aglisia Christy; Syadzadhiya Qothrunada Zakiyayasin Nisa (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
IPAL sludge in the Industrial Estate until now has not been able to be utilized properly, the utilization of IPAL sludge into flower pots is one of the efforts to overcome the problem of IPAL sludge waste. The purpose of this study was to determine the variations in each experiment, the characteristics of flower pots from IPAL sludge in each experiment, and the difference in ratios in each experiment. The method used is the solidification methods, which is the process of adding materials that can solidify waste to form a solid waste mass. Experiments were conducted with different mixtures of old newspapers, water, and cement to produce optimal flower pots. Of the three experiments that have been carried out, all experiments were carried out successfully and obtained the same ratio results, but have different characteristics. The implementation of this method is expected to be an example of sustainable waste management and provide benefits to the environment and society, and has the potential to support farming activities and can be a superior product in the handicraft business.